Potent Anti-Inflammatory Effects of Tetracyclines on Human Eosinophils - Gehring, Manuela; Wieczorek, Dorothea; Kapp, Alexander; Wedi, Bettina (Frontiers in Allergy, 2021)
Eosinophils are potent pro-inflammatory cells. Not only in allergic diseases but also in other diseases there is a need for treatment strategies to induce resolution of eosinophil-mediated inflammation. During the last years beneficial non-antibiotic activities of tetracyclines (TCNs) have been shown in different diseases in which eosinophils play a role, for example, asthma and bullous pemphigoid. The working mechanism of these effects remains to be clarified. Aim of the present study was to investigate the effects of TCNs on eosinophils. Flow cytometry analysis of apoptosis, mitochondrial membrane potential, activation of caspases, intracellular H2O2 and calcium, surface expression of eosinophil activation markers was performed in highly purified peripheral blood eosinophils of non-atopic donors. Tetracycline hydrochloride, minocycline and doxycycline significantly induced eosinophil apoptosis. All TCNs were able to significantly overcome the strong survival enhancing effects of pro-eosinophilic cytokines and staphylococcus aureus enterotoxins. Tetracycline hydrochloride induced eosinophil apoptosis was accompanied by intracellular production of hydrogen peroxide, loss of mitochondrial membrane potential and activation of caspases. Moreover, tetracycline hydrochloride significantly down regulated eosinophil surface expression of CD9 and CD45, and of the activation markers CD11b and CD69, but not of CD54, CD63, or CD95. Our data, propably for the first time, point to a potent anti-inflammatory role of TCNs on eosinophils.